The influence of fixed‐route taxi on road accidents and air pollution - Komarov, Jury; Fedotov, Vitali (Transport, 2006)
The development of market economy in Russia expands the need for movement of groups of people of large mega cities on time to a place at simultaneous reduction of the number of groups with identical purposes. Therefore for many cities a wide use of fixed‐route taxis the service of passengers at a constant increase of the numbers of routes and the numbers of transport units was characteristic. At the certain intensity of the movement of fixed‐route taxis on separate sites of city highways the transport stream and the changing quality of environment raises the risk of road accident and becomes ecologically unsafe. The results of the estimation of the negative influence of fixed‐route taxis in comparison with other categories of vehicles are presented. The research was made on city highways running through the zones with a greater number of cultural and community places, shopping centers and administrative establishments. Perspective ways of the increase of traffic safety and the decrease of concentration of harmful emissions are offered.First Published Online: 27 Oct 2010